Superconducting depression in thin films of YBa2Cu3O7-¿ based on the variation of the relative humidity and the time - J. C. Caicedo (Superficies y vacío, 2007)
Thin films of YBa2Cu3O7-δ grown on SrTiO3 (100) single crystal substrates by sputtering DC technique to high oxygenpressures were put under different conditions of relative humidity from 24 to 100% and different times of exposition. Theelectrical, morphologic and structural characteristics of the films by means of curves R-T, atomic force microscopy(AFM) and X-ray diffraction (XRD) were analyzed. The effect on structural and transport properties with theenvironmental conditions of relative humidity and with time were systematically studied. Samples under relative humidityaround 24% measured just later of deposition showed a critical temperature (TC) of 92 K, and thin films exposed around90% of relative humidity with times greater to 104 s (1 day) showed a TC of 16 K, while samples under a relative humidity100% do not showed the superconductive phase. The degradation´s causes of superconductive properties in this systemwere investigated.